Some experimental aspects of absolute configuration determination using single crystal X-ray diffraction - Thompson, A; Jenkinson, S; Fleet, G (Elsevier, 2017)
Students of single crystal X-ray diffraction are often give advice as to how best to collect their data when attempting absolute configuration determination. These 'rules' often have more grounding in gut-feeling than evidence. Thus, in an effort to provide advice and evidence that today's crystallographers can pass onto to tomorrow's young scientists, we present a systematic study of 1-deoxy-l-arabinitol, a straight chain sugar which crystalises well in the space group I41.